Risk Modelling and Management: An Overview - Chia-Lin Chang; David E. Allen; Michael McAleer; Teodosio Perez Amaral (Tinbergen Institute, 2013)
The papers in this special issue of Mathematics and Computers in Simulation are substantially revised versions of the papers that were presented at the 2011 Madrid International Conference on “Risk Modelling and Management” (RMM2011). The papers cover the following topics: currency hedging strategies using dynamic multivariate GARCH, risk management of risk under the Basel Accord: A Bayesian approach to forecasting value-at-risk of VIX futures, fast clustering of GARCH processes via Gaussian mixture models, GFC-robust risk management under the Basel Accord using extreme value methodologies, volatility spillovers from the Chinese stock market to economic neighbours, a detailed comparison of Value-at-Risk estimates, the dynamics of BRICS's country risk ratings and domestic stock markets, U.S. stock market and oil price, forecasting value-at-risk with a duration-based POT method, and extreme market risk and extreme value theory.
urn:NBN:nl:ui:15-1765/40419
Keywords: C14; C32; C53; C58; G11; G32; 330; Currency hedging strategies; Basel Accord; risk management; forecasting; VIX futures; fast clustering; mixture models; extreme value methodologies; volatility spillovers; Value-at-Risk; country risk ratings; BRICS; extreme market risk; Währungsspekulation; Basler Akkord; Portfolio-Management; Volatilität; Spillover-Effekt; Risikomaß; Länderrisiko; Extremwerttheorie; BRICS-Staaten